Analysis and methods of seismic risk in the historic urban areas: the case study in city of Salerno - Alessandra Landi (Tema, 2015)
The research described in the abstract presents a procedure to address risk assessment of large-scale urban systems with the aim to contribute at the development of risk mitigation policies for downtowns buildings. The observation of the earthquakes effects in Italy clearly highlights the role of the high vulnerability of the existing building on the consequences in terms of casualties and damage, rather than the severity of seismic events, especially in historical contexts. The objective of this study is to propose a procedure and a tool for the assessment and mitigation of seismic risk in urban areas.